Digital divides and bridges: equity implications of EdTech in ESL education - Yousofi, Rohullah; Golzar, Jawad; Yacoub, Omar (Frontiers in Education, 2025)
Despite the increasing integration of technology in education, digital inequities persist among ESL students, particularly in under-resourced academic settings. This explanatory mixed-methods study examined digital equity among undergraduate ESL students in the English Department of an Afghan public university, drawing on data from 78 questionnaires and six in-depth interviews. Thematic and statistical analyses revealed that while students reported high access to personal technological devices for language learning, they faced significant constraints in accessing computer laboratories and developing digital English learning materials. Additionally, limitations were observed in their engagement with technology-enhanced educational research. The findings indicated no statistically significant correlations between digital equity and gender, academic year, or socioeconomic status. Both students and instructors encountered these challenges, underscoring the urgent need for institutional strategies to mitigate digital disparities in higher education. Ultimately, the study concluded with several pedagogical implications.